2009
DOI: 10.1063/1.3272015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moisture on the photon-enhanced negative bias thermal instability in Ga–In–Zn–O thin film transistors

Abstract: We investigated the impact of photon irradiation on the stability of gallium-indium-zinc oxide (GIZO) thin film transistors. The application of light on the negative bias temperature stress (NBTS) accelerated the negative displacement of the threshold voltage (Vth). This phenomenon can be attributed to the trapping of the photon-induced carriers into the gate dielectric/channel interface or the gate dielectric bulk. Interestingly, the negative Vth shift under photon-enhanced NBTS condition worsened in relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
147
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(150 citation statements)
references
References 16 publications
2
147
1
Order By: Relevance
“…20,21 Similarly, adsorbed water molecules have been reported to act as donor-like surface states, 22 which causes negative DV TH shift. 13 However, Kim et al 23 water assisted oxygen absorption lead to a significant V TH shift under PBS. 24 Further, it is believed that the adsorbed water molecules at the back channel can diffuse towards the channel/gate dielectric interface, 25 generating a large number of metastable gap states leading to a large number of trapped electrons and eventual increase in hole carrier density, and thus exhibiting larger negative DV TH under NBS.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 Similarly, adsorbed water molecules have been reported to act as donor-like surface states, 22 which causes negative DV TH shift. 13 However, Kim et al 23 water assisted oxygen absorption lead to a significant V TH shift under PBS. 24 Further, it is believed that the adsorbed water molecules at the back channel can diffuse towards the channel/gate dielectric interface, 25 generating a large number of metastable gap states leading to a large number of trapped electrons and eventual increase in hole carrier density, and thus exhibiting larger negative DV TH under NBS.…”
mentioning
confidence: 99%
“…[2][3][4] Although zinc oxide TFTs with good field-effect mobility have been reported using various deposition techniques, [5][6][7][8][9][10] the stability of ZnO and other oxide-based TFTs under gatebias stress is a major concern for display applications. [11][12][13][14] Further, the increased temperature of display devices due to prolonged use or operation under harsh conditions can significantly shift the threshold voltage of the pixel-TFTs, 14,15 which would affect the performance of the corresponding device. It has been reported that appropriate doping of the semiconductor layer could improve the gate-bias stress stability of oxide based TFTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, it has been found that the stressed devices spontaneously recover to their initial state after a relaxation period without any thermal annealing. Also, it is important to note that the V th shift is significantly accelerated by applying two stress conditions simultaneously (e.g., negative gate-bias illumination stress) [157]. Although several groups have proposed a variety of possibilities such as oxygen vacancy, hole trapping, and electron injection, the origin of the related degradation mechanism is still unclear and under investigation.…”
Section: Stable and Reliable Oxide Tftsmentioning
confidence: 99%
“…Owing to their transparency and higher mobility compared to the amorphous silicon TFTs, a-IGZO TFTs have been studied widely, and various integrated circuits, such as the pixel circuit, scan drivers, inverter, ring oscillator, and logic gates, have been reported [5][6][7][8][9][10][11][12][13][14]. As p-channel operation is difficult due to the large density of states below the Fermi level, a-IGZO TFT circuits have been implemented with only n-channel TFTs.…”
Section: Introductionmentioning
confidence: 99%